Religious and spiritual coping among diabetic patients - Suhaimi, Atikah; Mamat, Nik Mazlan (2018)
Patients who are spiritual may apply their beliefs when coping with illness, pain, and life stresses. Studies indicated that those who are spiritual tend to have a more positive outlook and a better quality of life. The aim of the present study is to explore the level of religious and spiritual coping among diabetic patients.